Complaints of Asthenopia Symptoms in-office Employees - Chita Widia (Jurnal Vokasi Indonesia, 2021)
An Eyes health problem that can be experienced by employees is asthenopia. The purpose of this study is to address complaints of Asthenopia symptoms in the employees of one of the offices in Tasikmalaya city in 2020. This research uses a descriptive quantitative research method, a cross-sectional design. In this study, to collect data, the tool used was a questionnaire. Research results found that the most asthenopia symptoms felt by employees of one of the offices in the City of Tasikmalaya were shaded vision when looking at objects, glare when working at a computer, difficulty focusing while working at the computer, and shoulder or shoulder pain when working at a computer. work on the computer. 28 people (70%) out of 40 employees felt this way.